Strategic management perspective on digital transformation in PT Schneider Electric Manufacturing: The Smart Factory Program - Mahayoni, Ida Ayu (Universitas Pendidikan Nasional, 2025)
This study explores the digital transformation journey of PT Schneider Electric Manufacturing Batam through theimplementation of its Smart Factory Program, grounded in the principles of industry 4.0. Using a qualitativelibrary research method, data were gathered from books, scientific journals, and official company sources toanalyze how the integration of digital technologies addresses critical operational challenges. The study identifieskey issues such as insufficient oversight of performance, frequent equipment failures, and the need for scalabledigital solutions across facilities. Through thematic analysis, eight strategic solutions emerged, including supplychain efficiency, agile management, process optimization, asset performance management, operatorempowerment, reliability enhancement, energy efficiency, and social engagement. These strategies not onlyimproved operational efficiency and agility but also supported environmental sustainability and customersatisfaction. The findings highlight that a well-aligned digital transformation strategy, supported by crossfunctional collaboration and tec